Mass Spectrometric Back Reaction Screening of Quasi‐Enantiomeric Products as a Mechanistic Tool. Issue 6 (15th July 2016) - Isenegger, Patrick G.; Pfaltz, Andreas
Abstract: In this account, we discuss a mass spectrometric method that enables unambiguous identification of intermediates involved in the enantioselective step of a catalytic cycle. This method, which we originally developed for rapid evaluation of chiral catalysts, is based on monitoring the back reaction of mass‐labeled quasi‐enantiomeric products by ESI‐MS. In this way, the intrinsic enantioselectivity of a chiral catalyst can be determined directly by quantification of catalytically relevant intermediates. By comparing the results from the forward and back reaction, direct evidence for the involvement of a catalytic intermediate in the enantioselective step can be obtained. In addition, insights about the energy profile of the catalytic cycle may be gained. The potential of back reaction screening as a mechanistic tool is demonstrated for organocatalytic aldol reactions, 1, 4‐additions of aldehydes to nitroolefins, Diels–Alder reactions, Michael additions, and Morita–Baylis–Hillman reactions. Abstract : Observing back and forth : Mass spectrometric back reaction screening of quasi‐enantiomeric products may serve as a valuable tool for examining the mechanism of an enantioselective catalytic process. By comparing the results from the forward and back reaction, direct evidence for the involvement of a catalytic intermediate in the enantioselective step can be obtained. The potential of this method is demonstrated for various organocatalytic asymmetric reactions.